Semeadora de tração humana: projeto informacional e conceitual - Stefanello, Giusepe (2013)
The crops of corn and beans are sown on a large number of small farms where conventional tillage is commonly used. The farmers are interested in adopting no tillage farming. However, small planters suited for this purpose are not available in the market. The portable hand seeder (jab-type) was found to be used for more than half of these farmers, including direct seeding, in southern Brazil. Despite the positive factors of their use, there are field capacity and operating performance constraints as well as ergonomic problems. Companies are not interested in designing equipment better suited for this segment, continuing to produce old-fashioned planters. It is urgent to develop equipment of this size in order to enhance the sowing quality of these crops and to reduce the difficulty of the work of these farmers. The aim of this work was to conduct informational and conceptual design phases of a human-powered planter for direct seeding of corn and beans employing a design methodology. Drill concepts capable of performing tillage and no-tillage seeding have been developed, focusing on real technological needs related to the cultivation of these crops. One was chosen, among the concepts of the planters, which evolved into a final design, using currently existing principles of solution, obtaining the design of a push punch planter with superior characteristics when compared with the planters currently available. The concept is formed by a tubular steel frame, a ring-type vertical seed meter, nine punchers, depth gauge wheels and closure and firming wheel, enabling sowing quality, minimum soil disturbance and hence minimum energy demand